Clinical and functional features of penetrating keratoplasty in the Kingdom of Jordan. A single-center experience - M. A. Tanash; M. A. Frolov; P. A. Gonchar; G. N. Dushina; L. T. Ababneh (Вестник трансплантологии и искусственных органов)
Objective: to determine the indications for penetrating keratoplasty (PK) in the Kingdom of Jordan and evaluateits clinical and functional outcomes. Materials and methods. 213 patients underwent PK at the ophthalmology department of King Abdullah University Hospital (KAUH) in Jordan from January 1, 2010 to December 31, 2018. While 196 (92.2%) patients were operated on in one eye, 17 (8.8%) underwent PK in both eyes. For all patients, the best corrected visual acuity (BCVA) was checked using the Snellen table and compared with the BCVA before surgery; biomicroscopy of the anterior segment of the eye, as well as applanation tonometry, were carried out. Results. Keratoconus was found to be the most common indication for PK – 154 patients (73.2%). For all patients, the BCVA improved from 0.08 before surgery to 0.25 after surgery. Conclusion. Keratoconus is the most common indication for PK in both men (97, 71.3%, p < 0.05) and women (57, 74%, p < 0.05) in the Kingdom of Jordan. PK is an effective method for treating various corneal disorders.